Comparative Study between 12 and 15 Lead Electrocardiograms for Evaluation of Acute Posterior Myocardial Infarction - Wahib, SMA; Islam, AEMM; Haque, MM; Hossain, SMD; Kamal, MM; Ali, SY; Mahabub, SMEE (Cardiovascular Journal, 2012)
Background: The ECG diagnosis of acute posterior infarction has traditionally been based on the presence of ST segment depression on the pericardial chest leads. However, such ST segment depression is neither specific nor sensitive for the diagnosis of a posterior infarction. Detection of ST segment elevation in V7- V9 in 15 lead ECG can help in early diagnosis of acute Posterior myocardial infarction. Method: Total of 100 patients Inferior myocardial infarction was evaluated by Electrocardiography in standard 12 lead and 15 lead. The patients were categorized into group I having posterior/ and or associated changes and group II having without posterior changes in ECG. Echocardiography and LVgraphy was done to evaluate the posterior wall movement. Result: For diagnosis of posterior myocardial infarction, 43.3% sensitivity and 95.1% specificity was found in 12 lead ECG, whereas in 15 lead ECG it was 80.0% sensitivity and 95.1% specificity. Conclusion: 15 Lead ECGs (including V7-V9) more sensitive than 12 lead ECGs in diagnosis of acute posterior myocardial infarction. Patient with inferior myocardial infarction or anterior ischemia developed more complications if associated with acute posterior myocardial infarction. 15 lead ECGs can routinely be used in patients with ischaemic type of chest pain. DOI: http://dx.doi.org/10.3329/cardio.v4i2.10460 Cardiovasc. j. 2012; 4(2): 153-163